Policy, politics and leadership in slum upgrading: A comparative analysis of Harare and Kampala. (December 2018) - Muchadenyika, Davison; Waiswa, Jeremy
Abstract: Slum upgrading is one of the preferred options in dealing with ubiquitous informality in cities across the world. Drawing on experiences in two African cities namely Harare and Kampala; the article focuses on the role of policy, politics and leadership in slum upgrading. This paper is based on interviews conducted with urban leaders and managers, politicians, slum dwellers federation members and government officials. With regards to slum upgrading, the paper makes three arguments. First, policies guiding upgrading should evolve gradually over time, taking into consideration lessons learned. Second, tensions in party-politics tend to undermine slum upgrading programmes. This is mainly because of the vulnerability of informal settlers who are often used as sources and resources for political agency. Third, leadership at the city level plays a fundamental role in diffusing party-politics and championing inclusive municipal governance, and development. Highlights: Policies guiding upgrading should evolve gradually over time, taking into consideration lessons learned. Tensions in party-politics tend to undermine slum upgrading programmes Leadership at the city level plays a key role in diffusing party-politics and championing inclusive municipal governance.